DESIGN ARCHITECTURE ENTERPRISE UNTUK OPTIMALISASI PENJUALAN DAN LAYANAN PURNA JUAL AIR CONDITIONER PADA PT. BIRU LANGIT GEMILANG - Fiqri Fadilah; Arief Rahman; Biktra Rudianto (Jurnal Manajamen Informatika Jayakarta, 2025)
This study aims to design an enterprise architecture (AE) design for Optimizing Sales and After-Sales Service of Air Conditioners at PT. Biru Langit Gemilang, a company that sells air conditioners. This study explains the challenges faced by the company due to the absence of a system that connects the sales and finance divisions. This causes information delays and miscommunication. In today's digital era, it is very important for companies to have an integrated information system so that operations and decision-making can run smoothly. In this study, we used the AE design method with the TOGAF framework, which produces a blueprint for business, application, data, and technology architecture. The results of the study indicate that AE design can help integrate data and communication between divisions, thereby increasing operational efficiency and customer satisfaction. From this study, PT. Biru Langit Gemilang needs to utilize information systems and technology better to align business and technology strategies, as well as improve service and marketing performance. We also suggest that further research continue the TOGAF ADM phases and conduct cost analysis to ensure the successful implementation of the integrated system.